PsycEXTRA Dataset 2004
DOI: 10.1037/e609162007-001
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers in the United States: Sexual Activity, Contraceptive Use, and Childbearing, 2002

Abstract: Methods-In-person interviews using laptop computers. Among the total sample of males and females 15-44 were 1,150 females and 1,121 males aged 15-19. Response rate for teenagers was 81 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
475
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(508 citation statements)
references
References 0 publications
25
475
2
6
Order By: Relevance
“…Indeed, Brückner & Bearman showed that Add Health pledgers were as likely as nonpledgers were to use condoms at their most recent intercourse [9]. Still, failure to use a condom at first sex is important, as the risk of teen pregnancy is considerably higher among those who do not use condoms at first sex [32].Our study also sheds new light on the characteristics that distinguish pledgers from nonpledgers. Compared to youth who do not pledge, pledgers are more strongly religious, their parents more closely monitor their behavior, their friends and parents are more often opposed to their having sex, they are more likely to join clubs and participate in community activities, they are less likely to expect that having sex will lead to positive consequences, and they have lower sex self-efficacy.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, Brückner & Bearman showed that Add Health pledgers were as likely as nonpledgers were to use condoms at their most recent intercourse [9]. Still, failure to use a condom at first sex is important, as the risk of teen pregnancy is considerably higher among those who do not use condoms at first sex [32].Our study also sheds new light on the characteristics that distinguish pledgers from nonpledgers. Compared to youth who do not pledge, pledgers are more strongly religious, their parents more closely monitor their behavior, their friends and parents are more often opposed to their having sex, they are more likely to join clubs and participate in community activities, they are less likely to expect that having sex will lead to positive consequences, and they have lower sex self-efficacy.…”
mentioning
confidence: 71%
“…Indeed, Brückner & Bearman showed that Add Health pledgers were as likely as nonpledgers were to use condoms at their most recent intercourse [9]. Still, failure to use a condom at first sex is important, as the risk of teen pregnancy is considerably higher among those who do not use condoms at first sex [32].…”
Section: Discussionmentioning
confidence: 99%
“…Teen childbearing is believed to be influenced by a different set of decisions than is adult fertility (Levine 2001). Many teens are deciding whether to initiate sexual activity, or whether to initiate sex within the context of their current relationship (Abma et al 2010), whereas adults are typically sexually active. As a result, teens have three behavioral margins through which to react to economic news (sexual activity, contraception, and abortion), while the vast majority of adults have only two (contraception and abortion).…”
Section: Introductionmentioning
confidence: 99%
“…5 Ten percent of young women who had first had sex in their teenage years reported that their first time was involuntary, and the younger they were, the more likely that was the case. 6 content, yet only 14% of sexual incidents mention any risks or responsibilities of sexual activity. 8,9 Talk about sex on TV can occur as often as 8 to 10 times per hour.…”
Section: Introductionmentioning
confidence: 99%